Juridical Protection For Consumers Using The Online Applications - Iskandar, Orion; Al Afghani, M. Mova; Ratnawaty, Latifah (JURNAL MAHASISWA YUSTISI, 2023)
(P2P) Peer to Peer Lending Accessible over the Internet, lending is a programme that offers cash loan services. The Covid-19 outbreak that devastated Indonesia last year continues to have an impact on the people who are living in poverty given the present economic climate. Since the goal of this study is to identify various methods of consumer protection against legitimate online loans, how these efforts may be implemented to guarantee regulation-legislation, and how to assess the role of the in consumer protection. The information received under the Code of Commercial Law, Act No. 8 of 1999 on Consumer Protection, POJK No. 77/2016 on Information Technology-Based Money Loan Services, Law No. 11 of 2008, and Act No. 19 of 2016 on Electronic Information and Transactions, will thereafter be used. The governing parties' and their ranks' actions will determine how this all turns out, and they have a heavy burden of duty in being able to put a stop to this wrongdoing and save the rank with accurate information.